2022
DOI: 10.1021/acscentsci.1c01024
|View full text |Cite
|
Sign up to set email alerts
|

Bone-Specific Enhancement of Antibody Therapy for Breast Cancer Metastasis to Bone

Abstract: Despite the rapid evolution of therapeutic antibodies, their clinical efficacy in the treatment of bone tumors is hampered due to the inadequate pharmacokinetics and poor bone tissue accessibility of these large macromolecules. Here, we show that engineering therapeutic antibodies with bone-homing peptide sequences dramatically enhances their concentrations in the bone metastatic niche, resulting in significantly reduced survival and progression of breast cancer bone metastases. To enhance the bone tumor-targe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Antibody-drug conjugates (ADCs) represent a promising approach exemplified by the DESTINY-Breast03 trial of trastuzumab deruxtecan, which demonstrated substantial improvements in overall patient survival for pre-treated metastatic HER2-+ breast cancer ( Hurvitz et al, 2023 ). Experimentally, antibody-drug conjugate Trastuzumab with a hydroxyapatite-binding bone-homing peptide exhibits enhanced therapeutic efficacy in vivo , selectively delivering the agent to the bone metastatic niche ( Tian et al, 2022 ). Overall, many promising new strategies are in development to improve the treatment of metastatic breast cancer which rely on features specific to the metastatic niche to improve therapeutic delivery and increase sensitivity.…”
Section: Targeting the Metastatic Nichementioning
confidence: 99%
“…Antibody-drug conjugates (ADCs) represent a promising approach exemplified by the DESTINY-Breast03 trial of trastuzumab deruxtecan, which demonstrated substantial improvements in overall patient survival for pre-treated metastatic HER2-+ breast cancer ( Hurvitz et al, 2023 ). Experimentally, antibody-drug conjugate Trastuzumab with a hydroxyapatite-binding bone-homing peptide exhibits enhanced therapeutic efficacy in vivo , selectively delivering the agent to the bone metastatic niche ( Tian et al, 2022 ). Overall, many promising new strategies are in development to improve the treatment of metastatic breast cancer which rely on features specific to the metastatic niche to improve therapeutic delivery and increase sensitivity.…”
Section: Targeting the Metastatic Nichementioning
confidence: 99%
“…Additionally, the high molecular-weight (MW) materials guarantee facile formulation into nanocarriers for the loading of cargos, facilitating the treatment of bonerelated diseases. [26][27][28][29] However, few studies focused on the impact of structural parameters of anionic polypeptides on their bone-targeting ability, limiting the design of polypeptidebased, bone-targeting nanocarriers.…”
Section: Introductionmentioning
confidence: 99%
“…[11,12] It also helps to prevent potential side effects after a systemic administration. [13] However, current studies on TSPs have mainly been limited to the targeting and therapeutic functions of the peptides themselves. [14,15] The identification of potential peptide receptors on the cancer cell has seldom been reported.…”
mentioning
confidence: 99%